Effectiveness of integrase strand transfer inhibitor-based regimens in HIV-infected treatment-native individuals - Rossetti, Barbara (2021)
Publisher Copyright: © 2021 The Author(s) 2021. Published by Oxford University Press on behalf of the British Society for Antimicrobial Chemotherapy. All rights reserved.